Opressão, ativismo e cidadania LGBT+: análise do processo de institucionalização e implementação da Lei Estadual nº 10.895/2017 - PB - Melo, Amanda Leal Barros de (2020)
Sexual and gender diversity is a current aspect in the manifestation of the human subjectivities and its sociabilities, as several historic records testify that, in spite of the patriarchal structure – and, therefore, cis-heteronormative – widely imposed on the majority of the historicized people, accompanies the very notion of humanity a verification of the existence of dissenting subjects, with regard to what, is currently denominated sexual orientation and gender identity. In the face of this, it prevailed and remains opposed with intense discrimination of structural order, a phenomenon that is also under the neologism of LGBTphobia, which, despite the absence of broader official statistics, results in a great number of murders, aggressions and other violations of the human rights of the LGBT+ segment. Actions of discrimination and intolerance result in the stigmatization and dehumanization of those who dare to transgress, in respect to themselves, places that for long have been delimited for the maintenance of the privileges of those who benefit with the permanence of an exclusionary social structure, which standardizes human desires and affections. This work, supported by the trend of critical pedagogy and under the method of content analysis, aims to discuss a current normative in the state of Paraíba, which is, the Law n. 10.895/2017-PB, known as the Law of the Posters against LGBTphobia, which is considered to be an instrument to combat the discrimination against the population concerned. For this purpose, this phenomenon will be discussed, implemented by means of actions and omissions, as well as regarding the performance of the LGBT+ militancy, from the international conjecture to the situation in the state of Paraíba, in order to combat the violations perpetrated and in the quest for full citizenship. Aiming to carry out the analysis situated in the Law of the Posters against LGBTphobia 13 people were interviewed, from the Law-proposer, to institutional agents related to the object of research and representatives of some LGBT+ militancy entities of Paraíba. It was found that the normative in question has great relevance in promoting the LGBT+ citizenship and education for diversity. It also confirms that in the current scenario of worsening of the Brazilian democratic crisis, the significance of the exercise of resistance on the part of the LGBT+ militancy is substantially raised so that this population, so precariously assisted, is not deprived of the advances already achieved.